Monsoons, Rivers, and Tides : A Water Sector Diagnostic of Bangladesh - George, Joseph (World Bank, Washington, DC, 2021)
Water has always been at the heart of Bangladesh’s remarkable development story. Avoiding flood-induced famines and attaining food security were the defining motives in Bangladesh’s water management since the pre-independent days.1 These helped expand flood-control and modernize irrigation, strengthening its agro-based economy. Later in the century, catastrophic cholera epidemics and the growing irrigation demand pushed extensive investments in shallow tube wells, which remain the primary water source across the country. Today, water-intensive industries such as ready-made garments and textiles make up more than 85 percent of its exports, steering the nation’s job market and rapid economic growth. These structural changes, combined with the pressures from high population growth and climate change uncertainties, have now become key factors shaping Bangladesh’s approach to water management. With the Bangladesh Delta Plan 2100 (BDP), the country has begun an ambitious and holistic water management strategy. The plan puts water at its center for economic development and poverty reduction, and offers an adaptive approach for devising investment plans under climate uncertainties.2 Its implementation is not without challenges, because it would require strong interagency coordination, capacity building, and vast financial resources. This report documents the role of water in Bangladesh’s economy and the major water-related challenges. It aims to help develop a common approach in the sector among the Government of Bangladesh (GoB), the World Bank Group, and development partners in alignment with the BDP goals, the GoB’s Eighth Five-Year Plan (8FYP), and the World Bank Country Partnership Framework. The diagnostic assesses evidence from data, literature, and official documents to produce a synthesis of water-related challenges, and concludes with a set of priorities for enabling growth and tackling poverty for the next decade. Each challenge or priority area may be cross-cutting or relevant to one or several BDP areas (hotspots).